Juvenile Huntington disease in Argentina - Emilia Mabel Gatto; Virginia Parisi; José Luis Etcheverry; Ana Sanguinetti; Lorena Cordi; Adrian Binelli; Gabriel Persi; Ferdinando Squitieri (Arquivos de Neuro-Psiquiatria)
ABSTRACT We analyzed demographic, clinical and genetic characteristics of juvenile Huntington disease (JHD) and it frequency in an Argentinean cohort. Age at onset was defined as the age at which behavioral, cognitive, psychiatric or motor abnormalities suggestive of JHD were first reported. Clinical and genetic data were similar to other international series, however, in this context we identified the highest JHD frequency reported so far (19.72%; 14/71). Age at onset of JHD is challenging and still under discussion. Our findings reinforce the hypothesis that clinical manifestations, other than the typical movement disorder, may anticipate age at onset of even many years. Analyses of JHD cohorts are required to explore it frequency in populations with different backgrounds to avoid an underestimation of this rare phenotype. Moreover, data from selected populations may open new pathways in therapeutic approaches and may explain new potential correlations between HD presentations and environmental or biological factors.